Analysis of Palatal Rugae Pattern in Angle’s Classification of Malocclusion using Dental Casts in Chengalpattu District, Southern India: A Cross-sectional Study - Kashish Kariya; KT Magesh; Ramya Mahalingam; M Sathya Kumar; R Aravindhan; A Sivachandran; R Swaathi (Journal of Clinical and Diagnostic Research)
Introduction: Palatal rugae are uneven, asymmetrical ridges of the mucous membrane that stretch laterally from the anterior one-third of the mid-palatine raphe to the incisive papilla. Rugae are generally unique and stable, suggesting applications in forensics and orthodontics. During the early stages of intrauterine life, the formation of palatal rugae is completed, while dental malocclusion in the permanent teeth develops several years after birth. The objective of the present study was to identify the length, number and orientation of palatal rugae in various malocclusion groups. Aim: To investigate potential correlations between Angle’s classification of malocclusion and the palatal rugae pattern. Materials and Methods: A cross-sectional observational study was conducted in the Department of Oral and Maxillofacial Pathology at SRM Kattankulathur Dental College and Hospital, Chengalpattu, Tamil Nadu, India. Data was collected from the years 2021 to 2024 and data analysis was done from October 2023 to April 2024. Study was carried out on 105 archival pretreatment dental casts, ranging in age from 18-35 years. The samples were categorised into class I, class II and class III according to Angle’s system of malocclusion. Bilaterally, the three most prominent anterior primary rugae were counted, and their pattern, length and orientation were noted. STATA 17 software was used for data analysis. Results: The mean±Standard Deviation (SD) age of the study group was 26.5±23.64 years. According to mean±SD length of rugae significantly more (p-value <0.05) primary rugae were found in class I (1.39±1.34 mm) compared to class II (0.59±1.17 mm) and class III (0.5±0.97 mm). Both wavy and curved patterns showed statistical significance with the type of malocclusion (wavy: p-value=0.0001 and curved: p-value=0.0013) when compared to the straight pattern (p-value=0.1498). Regarding the mode of orientation, converging (0.39±0.6) and diverging (0.29±0.52) patterns were found to be statistically insignificant among the three classes of malocclusion. Conclusion: The study demonstrated slight variations in the palatal rugae pattern between Angle’s malocclusion classes. An additional finding that differed significantly among the malocclusion groups was the length of the rugae. However, the results did not reveal a specific pattern that is unique to any one type of malocclusion.